2020
DOI: 10.1139/cjas-2019-0132
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of using a hybrid rye cultivar in feeding broiler chickens

Abstract: The aim of this research was to evaluate the effectiveness of the use of hybrid rye in rations for broiler chickens. The study covered 160 chickens split into four equal groups [I (control), II, III, IV] and kept for 42 d. Rye was introduced into the above-mentioned diets as a partial substitute for maize in the following quantities: (I), no rye; (II), 5% rye in starter feed and 10% rye in grower and finisher feed; (III), 10% rye in starter feed and 20% rye in grower and finisher feed; (IV), 15% rye in starter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The basic nutrients and fiber fractions of the Suceveana rye variety used for this study are shown in Table 2. The content of crude protein amounted to 133.3 g kg −1 DM and was higher than that (116.69 g kg −1 DM) determined by Milczarek et al (2020). The level of crude fat in the evaluated grain was low (12.7 g kg −1 DM) and in line with the findings of Alijošius et al (2016) who reported a lower mean content of this component.…”
Section: Nutrient Composition Of Ryesupporting
confidence: 82%
See 3 more Smart Citations
“…The basic nutrients and fiber fractions of the Suceveana rye variety used for this study are shown in Table 2. The content of crude protein amounted to 133.3 g kg −1 DM and was higher than that (116.69 g kg −1 DM) determined by Milczarek et al (2020). The level of crude fat in the evaluated grain was low (12.7 g kg −1 DM) and in line with the findings of Alijošius et al (2016) who reported a lower mean content of this component.…”
Section: Nutrient Composition Of Ryesupporting
confidence: 82%
“…The level of crude fat in the evaluated grain was low (12.7 g kg −1 DM) and in line with the findings of Alijošius et al (2016) who reported a lower mean content of this component. The content of crude fiber in hybrid rye amounted to 39.7 g kg −1 DM and was higher than that (28.17 g kg −1 DM) determined by Milczarek et al (2020). The energy level of about 14.2 MJ/ME kg −1 DM is only slightly lower than in wheat (14.7 MJ/ME kg −1 DM).…”
Section: Nutrient Composition Of Ryementioning
confidence: 62%
See 2 more Smart Citations
“…These include cereal offals, oilseed meals, brewer's dried grains, distillers dried grain with solubles (DDGS), etc. Besides, through research, lesser used feedstuffs such as barley, rye, sorghum, cassava and grain legumes are increasingly being processed for feeding [23][24][25][26][27][28]. Furthermore, other plant resources in the wild such as false yam [29] and forages [30] are being harnessed for feeding due to advances in feed processing technologies and analytical tools.…”
Section: Use Of Novel Feed Ingredientsmentioning
confidence: 99%